Pembelajaran Everyone Is Teacher Here Dan Pengaruhnya Terhadap Hasil Belajar Matematika Siswa - Musnaeni Musnaeni; Nasaruddin Nasaruddin (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2016)
The main problem in this research is the teachers who do not use effective learning methods. One interesting learning methods to be implemented is the Everyone Is Teacher Here methods. It gives the opportunity for each student to act as a teacher for his friends. The research is experimental study using pretest-posttest control design. The technique of collecting data through observation and tests. The population is all students of class IX SMP Muhammadiayah Palopo many as 43 students. Based on the results of descriptive data analysis showed that the control class and experimental class before treatment with less category with an average of 57.14 and 55.73. Meanwhile, after treatment showed that the control class is in the category simply mean = 71.81 and the experimental class in both categories with mean = 78.73. So we can conclude that there is influence in terms of qualitative and quantitative terms occur due to the different categories of learning outcomes and the average value of students, in other words, there is the effect of the application of Everyone Is Teacher Here methods the results of students' mathematics learning in SMP Muhammadiyah Palopo